Dactilógrafa se necesita: representaciones de las empleadas administrativas en Buenos Aires (1920–1940) - Graciela Queirolo (Centre de Recherches sur les Mondes Américains, 2009)
The act of making visible women’s paid work constitutes one of the emerging signs of the processes of modernization that have affected Argentina since the last decades of the XIX century, with special emphasis on the city of Buenos Aires. This paper intends to approach the world of female administrative assistants – specifically the typists –, who, having attained a certain level of education, could aspire to further qualifications that would enable them to obtain better positions in relation to those attainable by factory workers. Our aim is to analyze the representations of these employees in several literary texts so as to characterize the specificities that such discourses attributed to this segment of paid women’s labor. In this way, we will also tackle the coincidences and tensions between the representations of typists and the normative commands imposed by gender–oriented identity models.